FACT Device for Reactive Power Compensation in the Deregulated Electrical Power Environment - M. Packiasudha; S. Suja (Institute of Advanced Engineering and Science, 2015)
In the deregulating electricity market, many private sector power producers are participating actively. With growing number of the wind mills and solar power generation, the reactive power production will be more because of induction generator and inductive type load. Many blackouts have happened in the past decades due to more reactive power which lead to a decrease in the magnitude of real power. It is very essential to compensate the reactive power, increase the real power flow in the transmission line, increase the transmission efficiency, improve the system stability and be in a safer place to save the fossil fuels for the future. In this paper the importance of reactive power and its various compensation techniques are applied to a five bus deregulated test case modeled and analyzed. The simulations were done using Matlab Simulink, for various FACT controllers such as STATCOM, SVC, SSSC and UPFC compensation and the results were tabulated and compared.